Advances in epitope mapping technologies for food protein allergens: A review. (January 2021) - Zhou, Fanlin; He, Shudong; Sun, Hanju; Wang, Yongfei; Zhang, Yi
Abstract: Background: The incidence of food allergy has been increasing in recent years, but the prevention, diagnosis, and treatment of food allergy remain challenges in the world. Food allergen epitope mapping technology can help us identify the epitope sequence and structure, which is conducive to the development of food allergy prevention, diagnosis, and treatment methods. Moreover, the information about allergic epitopes also plays a positive role in the development of new hypoallergenic or non-allergenic food products in the industry. Scope and approach: This article systematically reviews state-of-art research progress and development trend of food epitope mapping technology based on the advantages and disadvantages as well as the potentials of each method. The future development direction and trend of food protein allergen epitope mapping technology were also discussed, with a view to providing a reference for the identification and characterization of food allergens. Key findings and conclusions: Compared with traditional technologies including peptide scanning technique, novel technologies have the advantages of high specificity, high sensitivity, high accuracy, and high-throughput. Although some progress has been made in the identification and characterization of food protein allergen epitopes, a large number of epitopes have not yet been identified so far. Some work is still needed for invention of new epitope mapping technology, establishment of systematic and comprehensive databases, and development of allergic omics in the future. Highlights: Specificity between IgE antibodies and epitopes is indicator of food allergy. Recent advances in techniques have enabled efficient prediction of epitopes. Current and development of food epitope mapping technologies were discussed. Epitope identification mechanism would be better understood. Diagnosis/prognosis of food protein allergies would be more effectively.